2004
DOI: 10.1111/j.1523-1739.2004.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Conspecific Attraction and the Conservation of Territorial Songbirds

Abstract: Conspecific attraction, the tendency for individuals of a species to settle near one another, is well described in colonial species, especially birds. Although this behavior may occur in territorial birds, evidence has been lacking. If territorial birds do exhibit this behavior, it would have major conservation implications. Birds could potentially be attracted to specific sites with artificial stimuli, making conservation of those species more efficient. In 2001 and 2002, we tested whether conspecific attract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
209
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(214 citation statements)
references
References 43 publications
3
209
0
2
Order By: Relevance
“…We did not include any vocalizations that were typical of aggressive interactions between flycatchers. Similar to other studies of conspecific attraction, no broadcasts were used at control sites (Ward and Schlossberg 2004).…”
Section: Automated Broadcastsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include any vocalizations that were typical of aggressive interactions between flycatchers. Similar to other studies of conspecific attraction, no broadcasts were used at control sites (Ward and Schlossberg 2004).…”
Section: Automated Broadcastsmentioning
confidence: 99%
“…Why Willow Flycatchers so rarely recolonize newly restored, high-quality habitat remains unknown but there is some indication that behavioral constraints may play a role. Some territorial passerine species are known to rely on social cues such as the presence of conspecifics' songs to assess the quality of possible breeding habitat and are reluctant to establish territories where conspecifics are not present (Muller et al 1997, Ward and Schlossberg 2004, Andrews et al 2015. For many species, especially those with short breeding seasons, the presence of other members of their species might be used as an indirect way for naïve individuals to infer habitat quality and quickly find a suitable territory without investing substantial time (Hahn and Silverman 2006).…”
Section: Introductionmentioning
confidence: 99%
“…By deploying conspecific cues such as decoys or recordings in unoccupied but suitable areas, researchers have found that they can attract individuals to settle and breed in these areas [9]. While this technique was originally employed to re-establish breeding populations of colonial-nesting waterbirds [13], it has since been tested in numerous avian species and is considered a viable tool for the conservation of threatened and endangered songbirds [9,11]. Other non-avian species have also been found to use a variety of conspecific cues when selecting habitat: common noctule bats (Nyctalus noctula) use acoustic cues to locate roosts [14], coral reef fish use chemical cues to find reef habitat [15], and bronze anoles (Anolis aeneus) make settlement decisions based on conspecific presence [16].…”
Section: Introductionmentioning
confidence: 99%
“…Conspecific attraction relies on the premise that individuals use conspecific presence when determining where to settle, resulting in individuals of the same species settling near each other [10][11][12]. By deploying conspecific cues such as decoys or recordings in unoccupied but suitable areas, researchers have found that they can attract individuals to settle and breed in these areas [9].…”
Section: Introductionmentioning
confidence: 99%
“…The various components of habitats, such as vegetation structure and habitat composition , Tome 2004, Remacha & Delgado 2009, Lopez et al 2010, may also play a role in nest site selection, influencing occupancy rate of artificial nest-boxes. Besides nest-box design and habitat characteristics, birds may use the presence/absence or breeding success of conspecifics and/or species with similar ecological requirements that provide valuable information on nest site suitability (Danchin et al 2001, Pajero et al 2004, Ward et al 2004.…”
Section: Introductionmentioning
confidence: 99%